The so-called eighth Stromateus by Clement of Alexandria: early Christian reception of Greek scientific methodology - Havrda, Matyáš (Philosophia antiqua, 2017)
Introduction: the riddle of the eighth Stromateus: questions and solutions -- The so-called eighth Stromateus ('Liber logicus') by Clement of Alexandria: Greek text, translation, and commentary